The Integration of Application-Based Instructional Technology in Arabic Language Teaching at Madrasah Aliyah: Teachers’ and Students’ Perceptions - Nafisa Hashifatuzahra; Dea Insan Agnia; Azka Fathur Robbani (Gunung Djati Conference Series, 2026)
This study aims to examine the forms of integration of application-based instructional technology in Arabic language teaching at Madrasah Aliyah (MA), including its planning, implementation, and assessment. It also seeks to explore teachers’ and students’ perceptions of the effectiveness of using digital applications, as well as to identify supporting and inhibiting factors in their application. Overall, the study is intended to understand the extent to which application-based technology can enhance the quality of Arabic language learning in MA. This research employs a descriptive qualitative approach aimed at providing an in-depth portrayal of the integration of application-based instructional technology in Arabic language teaching at Madrasah Aliyah (MA), based on the perceptions of teachers and students. This approach was selected because it enables the researcher to understand the meanings, experiences, and perspectives of the informants comprehensively within the natural learning context. The descriptive qualitative design emphasizes describing phenomena as they are, without manipulating variables, resulting in narrative data regarding experiences in using applications, their effectiveness in learning, as well as the challenges and opportunities that emerge during implementation. The findings indicate that the integration of application-based instructional technology in Arabic language teaching at MA is carried out systematically across the stages of planning, implementation, and assessment. Both teachers and students hold positive perceptions, as the applications enhance interactivity, material accessibility, and learning effectiveness. However, challenges such as teachers’ limited digital competence, inadequate infrastructure, unstable internet connectivity, and device distractions still impede optimal implementation. Nevertheless, the availability of devices and institutional support serve as important enabling factors that strengthen the integration of technology.